2006
DOI: 10.2174/092986706776360950
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin as a New Hepatoprotective Agent in Experimental Cholestasis: New Possibilities for an Ancient Medication

Abstract: Silymarin is a purified extract from milk thistle (Silybum marianun (L.) Gaertn), composed of a mixture of four isomeric flavonolignans: silibinin (its main, active component), isosilibinin, silydianin and silychristin. This extract has been empirically used as a remedy for almost 2000 years, and remains being used as a medicine for many types of acute and chronic liver diseases. Despite its routinely clinical use as hepatoprotectant, the mechanisms underlying its beneficial effects remain largely unknown. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 177 publications
0
69
0
1
Order By: Relevance
“…It prevents apoptotic and necrotic cell death in the liver (31) and retards the progression of alcohol-induced hepatic fibrosis (32). Silymarin is the natural product of most widespread use in the treatment of liver diseases (33), and it is sold over the counter all over the world (34). Its low toxicity encouraged researchers to use silymarin in long-term tests in chronic and severe liver conditions in humans, and its efficacy in the prevention of liver fibrosis and stimulation of liver regeneration was observed in alcoholic and nonalcoholic fatty liver diseases and in drug-and chemical-induced hepatic toxicity (35).…”
Section: Discussionmentioning
confidence: 99%
“…It prevents apoptotic and necrotic cell death in the liver (31) and retards the progression of alcohol-induced hepatic fibrosis (32). Silymarin is the natural product of most widespread use in the treatment of liver diseases (33), and it is sold over the counter all over the world (34). Its low toxicity encouraged researchers to use silymarin in long-term tests in chronic and severe liver conditions in humans, and its efficacy in the prevention of liver fibrosis and stimulation of liver regeneration was observed in alcoholic and nonalcoholic fatty liver diseases and in drug-and chemical-induced hepatic toxicity (35).…”
Section: Discussionmentioning
confidence: 99%
“…One of the best studied cholagogues is silymarin from milk thistle Silybum marianum, which is mixture of four isomeric flavonolignans; silibinin (most active component), isosilibinin, silydianin and silychristin. 18 Silymarin induces hepatic output of bile acids and bile acid-dependent choleresis, but does not affect bile acid-independent bile flow.…”
Section: Didenko Et Almentioning
confidence: 98%
“…Silymarin is also used for the treatment of Amanita phalloides mushroom poisoning (Desplaces et al, 1975;Hruby et al, 1983;Vogel et al, 1984). In vitro and animal studies have demonstrated the hepatoprotective properties of silymarin or silybin (a mixture of SB A and SB B ) (Fraschini et al, 2002;Hoofnagle, 2005;Crocenzi and Roma, 2006). Several clinical trials have shown an excellent safety profile for silymarin in humans (Fraschini et al, 2002;Ball and Kowdley, 2005;Dryden et al, 2006).…”
mentioning
confidence: 99%